Political suicide [compact disc, unabridged] - Palmer, Michael, 1942-2013 (Macmillan Audio, 2012)
Dr. Lou Welcome has been supervising Dr. Gary McHugh's recovery from alcoholism. Though McHugh hasn't been taking his AA program seriously, Lou sees progress and the two have become friends. After visiting a patient of his, Congressmen Elias Colston, McHugh is found unconscious in his wrecked car. Colston has been shot dead, and McHugh is the prime suspect, though he insists the congressman was dead when he got there. Lou investigates the murder and uncovers a deadly conspiracy.